2015
DOI: 10.1007/s10526-015-9706-z
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Trichoderma harzianum in the olive rhizosphere: time course of the root colonization process and interaction with the fungal pathogen Verticillium dahliae

Abstract: is a postdoctoral researcher skilled on integrated control of soilborne pathogens of woody plants, on the selection and characterization of biological control agents with special interest in the genera Trichoderma and Pseudomonas, and on the study of phytopathogen-biological control agent interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 45 publications
1
32
0
1
Order By: Relevance
“…Previous studies have demonstrated the value of CLSM for monitoring infection and colonization of herbaceous and woody hosts by V. dahliae (Prieto et al ., ; Zhang et al ., ), as well as for simultaneous visualization of this pathogen and the biocontrol strains P. fluorescens PICF7 and T. harzianum GFP22 (Prieto et al ., ; Ruano‐Rosa et al ., ). The use of the fluorescent transformant D V. dahliae V138I‐YFP, obtained in the present study, and of the commonly employed strain T. harzianum GFP22 (Chacón et al ., ; Samolski et al ., ; Alonso‐Ramírez et al ., ; Ruano‐Rosa et al ., ), allowed simultaneous examination of the growth of D V. dahliae and T. harzianum in olive and wild olive plants by means of CLSM. The newly developed V. dahliae YFP transformant proved suitable for the study because it did not show any difference compared with the wild type strain V. dahliae V‐138I regarding morphology and growth rate on different culture media.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous studies have demonstrated the value of CLSM for monitoring infection and colonization of herbaceous and woody hosts by V. dahliae (Prieto et al ., ; Zhang et al ., ), as well as for simultaneous visualization of this pathogen and the biocontrol strains P. fluorescens PICF7 and T. harzianum GFP22 (Prieto et al ., ; Ruano‐Rosa et al ., ). The use of the fluorescent transformant D V. dahliae V138I‐YFP, obtained in the present study, and of the commonly employed strain T. harzianum GFP22 (Chacón et al ., ; Samolski et al ., ; Alonso‐Ramírez et al ., ; Ruano‐Rosa et al ., ), allowed simultaneous examination of the growth of D V. dahliae and T. harzianum in olive and wild olive plants by means of CLSM. The newly developed V. dahliae YFP transformant proved suitable for the study because it did not show any difference compared with the wild type strain V. dahliae V‐138I regarding morphology and growth rate on different culture media.…”
Section: Discussionmentioning
confidence: 97%
“…Trichoderma harzianum GFP22, a GFP‐marked strain derived from the wildtype strain T. harzianum CECT 2413 (Spanish Type Culture Collection, Burjassot, Spain), kindly provided by Dr Ana Rincón (University of Seville, Spain), was used as the antagonistic fungus. Strains CECT 2413 (referred to as T34 strain) and GFP22 are commonly used in basic biocontrol (Lorito et al ., ) and CLSM (Samolski et al ., ; Alonso‐Ramírez et al ., ; Ruano‐Rosa et al ., ) studies, respectively. Monoconidial V. dahliae V‐138I isolate (Department of Crop Protection culture collection, Instituto de Agricultura Sostenible, CSIC, Córdoba, Spain; referred to as V‐138I strain), previously typed to lineage 1A, D pathotype and race 2 (Jiménez‐Díaz et al ., ), was used as a host in the transformation experiments to express yellow fluorescent protein (YFP) in V. dahliae .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, and regarding beneficial fungi, representatives of the genus Trichoderma were found in the rhizosphere of all cultivars but Chemlal de Kabylie and Llumeta. Species of this genus have been successfully used as BCA against VW of olive 46,47 .…”
Section: Discussionmentioning
confidence: 99%